The role of temperature and frequency on fretting wear of a like-on-like stainless steel contact - Jin, X.; Shipway, P.H.; Sun, Wei (Springer, 2017)
The influences of environmental temperature and fretting frequency on the mechanisms and rates of wear in a like-on-like 304 stainless steel contact were examined, and mainly attributed to changes in the mechanical response of the bulk material and to changes in the behaviour of the oxide debris formed in the fretting process. At low temperatures, wear proceeds by continual oxide formation and egress from the contact, whilst at high temperatures, the rate of wear is much reduced, associated with the development of oxide formed into a protective bed within the contact. The temperature at which the change between these two behaviours took place was dependent upon the fretting frequency, with evidence that, at this transition temperature, changes in behaviour can occur as the fretting test proceeds under a fixed set of conditions. An interaction diagram has been developed which provides a coherent framework by which the complex effects of these two parameters can be rationalised in terms of widely accepted physical principles.